Atribuţiile organelor vamale ale Republicii Moldova în domeniul protecţiei consumatorilor [Articol] - Erhan, Ianuș; Plotnic, Olesea (Academia de Administrație Publică, 2014)
The traceability of a product and placing it on the domestic market directly depends on the performance of its duties by Customs. Thus, Customs has the right to decide, on the basis of customs control, especially physical and documentary control, if goods entering the Republic of Moldova and intended to be placed in free circulation, meet the conditions of quality and compliance. In this context, the legal and institutional framework shall create for Customs all necessary conditions to fully apply its competence in the field of consumers’ protection at the highest level.
THE POWERS OF CUSTOMS BODIES OF THE REPUBLIC OF MOLDOVA IN THE FIELD OF CONSUMER PROTECTION
ОБЯЗАННОСТИ ТАМОЖЕННЫХ ОРГАНОВ РЕСПУБЛИКИ МОЛДОВА В ОБЛАСТИ ЗАЩИТЫ ПОТРЕБИТЕЛЕЙ